Hukum Dan Dharma Dalam Parāśara Dharmaśāstra Kajian Filsafat Hukum Hindu Metode Interpretasi Veda Śri Aurobindo - Ida Bagus Sudarma Putra; Ida Ayu Sri Kusuma Wardhani; Ni Kadek Surpi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The Parāśara Dharmaśāstra is a legal library dedicated to the Kali Yuga. The Dharmaśāstra literature stipulates that in each different era, a different legal system applies. The sages and kings determine which part is appropriate for the era. Because in Hinduism, the purpose of customary law or religion is to build order in life and the morality of society. The Parāśara Dharmaśāstra talks about law and dharma, both of which aim to build the moral order of civilized society. This article is a text study that specifically examines the text of the Parāśara Dharmaśāstra which is the smṛti of the Kali Age. The text study uses the Śri Aurobindo Vedic interpretation method. The advantage of Śri Aurobindo's interpretation method is that it examines the Vedic text in depth by paying attention to the purpose of the text being studied. Therefore, the interpreter will get the real meaning of both the language and the main purpose and for whom a text is intended. The Parāśara Dharmaśāstra is a law book that is still valid today. However, as a customary and religious law, not all slokas can apply absolutely because only adjustments are made to environmental conditions including world conditions in general. However, the laws and Dharma in this book will be able to provide moral guidance to build a religious society as well as to contribute in this modern era.